2021
DOI: 10.1093/bjs/znab134.041
|View full text |Cite
|
Sign up to set email alerts
|

167 The Experience and Outcomes of Elective Urgent and Cancer Surgery in A District General Hospital in The United Kingdom During Covid-19 Pandemic

Abstract: Background Many urgent and elective surgeries were postponed to cope with the Coronavirus disease (COVID-19) pandemic, with latest data found a substantial postoperative mortality risk (25·6%, 18.9%) after emergency and elective surgery, respectively. Our institution was one of the first trust to offer essential elective surgery using a “COVID-free” designated site during the start of the pandemic. The aim of this study is to analyse the clinical outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Italian and French studies respectively described an institutional policy to proceed with elective procedures for oncologic indications [ 6 , 7 , 21 ]. Eight studies reported a prohibition on hospital visitation [ 6 , 21 , 22 , 26 , 61 , 63 , 64 , 66 ]. One of these studies described telephonic updates to consenting patients’ relatives, provided by the Surgery Unit Chief [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Italian and French studies respectively described an institutional policy to proceed with elective procedures for oncologic indications [ 6 , 7 , 21 ]. Eight studies reported a prohibition on hospital visitation [ 6 , 21 , 22 , 26 , 61 , 63 , 64 , 66 ]. One of these studies described telephonic updates to consenting patients’ relatives, provided by the Surgery Unit Chief [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adequate stockage and preservation of PPE, especially for high-risk procedures, was widely recommended [ 7 , 18 , 24 , 26 , 58 , 60 , 65 ]. Demarcated areas for ‘donning and doffing’ were erected at U.K.-based and Italian institutions [ 6 , 63 ]. Lastly, one study discussed ensuring an ongoing supply of oncologic drugs, considering an increased reliance on non-surgical therapy at an Indian institution [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations